KAJIAN PENYIARAN PERSIDANGAN SECARA LIVE DALAM PERLINDUNGAN ANAK DAN PRINSIP PERSIDANGAN TERBUKA UNTUK UMUM - Dita Mulyani; Muhammad Rustamaji (Verstek, 2023)
This article was created to analyze the practice of the live broadcast of the trial. The existence of this practice means that everyone from all ages can participate in witnessing the live broadcast without any restriction, including minors. This article aims to find out the legal principle about the live broadcast of the trial in the child protection concept and the open court principle and to find out the limititations of open court principle on a live broadcast of the trial. This is a normative legal research using conceptual approach. This research shows that the live broadcast of the trials in child protection is carried out by ensuring child protection through the dissemination of useful information and educational materials from the social, cultural, educational, religious, and health aspests and pay attention to child’s importance. The obligations of the television media is to make sure that live broadcast of the trial include on clasification D for audience over the age of 18 years old. The limitation of the live broadcast of the trials is entirely on the role of the judges to determining the open court mechanism by pay attention to the characteristic of the case and to priority the litigants. Meanwhile the interests of broadcasting institution are accesoir after the limitation of the broadcasting law, KPI regulation, and law of criminal procedure.Keywords: Child Protection; Live Broadcast; Open Court principle; Television.